A comparative analysis of 3 sedation guidelines for patients undergoing subarachnoid anesthesia. Randomized, single blind clinical trial☆. Issue 2 (2015) - Bermúdez‐Guerrero, Francisco José; Gómez‐Camargo, Doris; Palomino‐Romero, Roberto; Llamas‐Bustos, William; Ramos‐Clason, Enrique
ABSTRACT : Introduction: : Sedation is defined as the set of actions aimed at having a quiet, comfortable, pain‐free patient during a diagnostic or therapeutic procedure without any bad memories. Since the standard regional anesthesia techniques used in clinical practice are relatively traumatic and painful procedures, sedation has been introduced to make these interventions more comfortable for the patient and to facilitate the patient's cooperation. Objective: : To establish the efficacy of three sedation guidelines in patients undergoing subarachnoid anesthesia. Methodology: : Experimental, randomized, prospective, single blind clinical trial comparing three guidelines for the sedation of patients undergoing subarachnoid anesthesia. Results: : All of the patients in the trial received anxiolysis, collaborated with the puncture and said that they would not be afraid to receive subarachnoid anesthesia in the future. There were no complications including respiratory depression, nausea, vomiting or any other complications reported with the use of the sedation guidelines. Patient satisfaction was high. Withdrawal reflex ( P = 0.0003) and puncture related pain ( P = 0.0069) were more common in the group using the intravenous midazolam‐only guideline and patient satisfaction with sedation was also lower in this group; however, the three guidelines showed good efficacy. Conclusions: : The three sedation guidelines presented were effectively used in subarachnoid anesthesia; the results were more favorable with the use of midazolam+ fentanyl or midazolam + ketamine. p‐2011‐1682 Colciencias. Registro # NCT0213664 (clinicaltrials.gov, prospectivo). RESUMEN : Introducción: : la sedación es un conjunto de acciones dirigidas a lograr que un paciente se encuentre tranquilo, cómodo, libre de dolor o de malos recuerdos mientras se realiza un procedimiento diagnóstico o terapéutico. Dado que las técnicas anestésicas regionales empleadas en la práctica clínica habitual son procedimientos relativamente traumáticos y dolorosos, se han asociado a sedación, para hacer este tipo de intervenciones más confortables para el paciente y hacer más fácil la colaboración del mismo. Objetivo: : determinar la eficacia de tres pautas de sedación en pacientes que van a ser sometidos a anestesia subaracnoidea. Metodología: : Estudio experimental, ensayo clínico, aleatorizado, prospectivo, simple ciego, en el cual se compararon tres pautas para sedación en pacientes sometidos a anestesia subaracnoidea. Resultados: : todos los pacientes del estudio tuvieron ansiolisis, colaboraron a la punción y refirieron que volverían a recibir una anestesia subaracnoidea sin temor, además no se reportaron complicaciones tales como depresión respiratoria, náuseas, vómitos u otra, con las pautas de sedación utilizadas, siendo alta la satisfacción por parte de los pacientes. El reflejo de retirada (P = 0, 0003) y el dolor a la punción (P = 0, 0069) se presentaron en mayor proporción en el grupo que usó como pauta solo midazolam intravenoso, en este mismo grupo hubo menor satisfacción con la sedación; sin embargo, las tres pautas mostraron una buena eficacia. Conclusiones: : Las tres pautas de sedación propuestas fueron eficaces para su uso en anestesia subaracnoidea, con mejores resultados cuando se usó midazolam más fentanilo o midazolam más ketamina. p‐2011‐1682 Colciencias. Registro # NCT0213664 (clinicaltrials.gov, prospectivo).